Korzyści i problemy wynikające ze stosowania amnestii podatkowej w świetle doświadczeń wybranych krajów UE - Brodzka, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Last changes introduced into the European tax information exchange system have caused the growing interest in tax amnesty programmes. The tax amnesty is perceived as an instrument which can strengthen the national tax system. Some of the EU member states have decided to use the solution in order to broaden the tax base and to bring the flowing capital back. Different variants of the tax amnesty programmes which were introduced in European countries have brought various effects. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 38-47